An inquiry into the theory, causes and consequences of monitoring indicators of health and safety at work - Konstantinos Pouliakas; Ioannis Theodossiou (Institute for the Study of Labor (IZA), 2010)
This paper engages in an interdisciplinary survey of the current state of knowledge related to the theory, determinants and consequences of occupational safety and health (OSH). First, it synthesizes the available theoretical frameworks used by economists and psychologists to understand the issues related to the optimal provision of OSH in the labour market. Second, it reviews the academic literature investigating the correlates of a comprehensive set of OSH indicators, which portray the state of OSH infrastructure (social security expenditure, prevention, regulations), inputs (chemical and physical agents, ergonomics, working time, violence) and outcomes (injuries, illnesses, absenteeism, job satisfaction) within workplaces. Third, it explores the implications of the lack of OSH in terms of the economic and social costs that are entailed. Finally, the survey identifies areas of future research interests and suggests priorities for policy initiatives that can improve the health and safety of workers.
Keywords: J17; J28; J81; K32; 330; Health; safety; indicators; accidents; diseases; absenteeism; Arbeitsschutz; Ergonomie; Sozialer Indikator; Arbeitsunfall; Fehlzeit; Erwerbsunfähigkeit; Soziale Kosten